“LA DANZA EN EL FORTALECIMIENTO DE LA MOTRICIDAD GRUESA EN LOS NIÑOS Y NIÑAS DE 4 AÑOS DE LA INSTITUCIÓN EDUCATIVA INICIAL 055 DE CHACHAPOYAS – 2023” - Gonzales Pimgus, Dayli Mayeli (2024)
The present research work entitled dance in the strengthening of gross motor skills in children of 04 years of the educational institution 055 of Chachapoyas, had the purpose of determining the use of dance in the strengthening of gross motor skills, oriented in an applied research within the quantitative approach, with pre-experimental design, having a population of 54 children in the ages of 03 to 05 years; and applied to a sample of 15 children from the age of 04 years, having dance and gross motor coordination as variables, applying 20 workshops aimed at improving the dimensions of gross motor skills, the results being the improvement of the levels of achievement going from the beginning level to the levels of process, achieved and outstanding, concluding that dance significantly improves gross motor coordination. This is demonstrated in Table 9, which refers to the results obtained in the gross motor development of the children, where the pre-test 15 children were in the beginning level, representing 100% of the total, thus demonstrating that they were at a very low level, on the other hand when applying the post-test we can observe a great difference having students in the process level equivalent to 27%, in the achieved level 40% and outstanding 33%, determining that the use of dance did help significantly to strengthen gross motor skills.